Lifetime seismic risk assessment of coastal highway bridges under corrosion, scour and liquefaction effects - ICASP14; Li, Yue; Xu, Bo; Wang, Xiaowei (My University, 2023)
Coastal highway bridges, particularly those with reinforced concrete members, are susceptible to chloride-induced corrosion in their lifetime due to the aggressive coastal environment. Such an adverse environment has also witnessed the susceptibility and vulnerability of these bridges to multi-hazard events during their service life; such events include, but are not limited to, scour and earthquake-induced liquefaction. While previous studies extensively assessed the lifetime performance of coastal highway bridges under multiple hazards, hardly any work has been conducted on the lifetime seismic performance of such bridges under the combined effects of corrosion, scour, and liquefaction. To fill in this gap, as well as to account for the vast uncertainties in the corroded reinforced concrete members of bridges and associated soil profiles, this study carries out a risk-informed assessment to understand individual and combined effects of corrosion, scour, and liquefaction. To this end, a typical coastal highway bridge is adopted as a testbed structure, which is simulated in OpenSees using a multi-dimensionally soil-structure modeling technique while considering various sources of uncertainties in structural, geotechnical, and environmental parameters. Through probabilistic seismic demand analyses and capacity modeling, fragility curves are generated for different scenarios including individual, combinations of two out of the three effects, and the combination of all three effects of corrosion, scour, and liquefaction. Together with probabilistic seismic hazard analyses, time-dependent seismic risk of coastal highway bridges can be obtained to better understand the roles of these effects in the lifetime performance assessment. This pilot study can facilitate risk-informed decision-supports on the life-cycle management of coastal highway bridges under the ever-changing multi-hazard threats.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED